ʿAyn al-Quḍāt on Chivalry - Rustom, Mohammed (Journal of Islamic ethics, 2020)
Abstract This article investigates the multi-dimensional presence of the important Persian Sufi concept of jawānmardī or chivalry in the writings of the famous 6th/12th century metaphysician, martyr, and mystic ʿAyn al-Quḍāt Hamadānī (d. 525/1131). The article begins by situating jawānmardī vis-à-vis its Arabic Sufi equivalent of futuwwa . Both of them convey a wide range of spiritual perfections ranging from wisdom and detachment to justice and pure generosity. Moreover, the article explores the specifically Persian emphasis on jawānmardī as an embodiment of the ideal type of lover of God. It will consequently be shown how, in the writings of such an influential figure as ʿAyn al-Quḍāt, jawānmardī is most prominently featured in three distinctive modes: an aspirational ideal, a realised concept, and the key to unlock the mystery of one of the greatest chevaliers, namely Iblīs.